INNOVATIVE LEADERSHIP OF KIAI IN ISLAMIC BOARDING SCHOOL EDUCATION MANAGEMENT: A CASE STUDY OF SURYALAYA ISLAMIC BOARDING SCHOOL - Mulyatno, Wolio (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Suryalaya Islamic Boarding School is a Sufism-based Islamic boarding school, as the leader of Sufism Mursyid Tarekat Qodiriyah Naqsyabandiyah. This study produces an innovative Sufism-based leadership model that integrates spiritual, social, and institutional dimensions in Islamic boarding school education management. Through a descriptive qualitative approach, this study reveals that the Leadership Innovation Management of KH Ahmad Shohibul Wafa Tajul Arifin at Suryalaya Islamic Boarding School is very beneficial for the needs of the wider community, As a result, KH Ahmad Shohibul Wafa Tajul Arifin as the caretaker of Suryalaya Islamic Boarding School has made many innovations, especially in community education in the form of Talqin Dzikir policies, organizational forums, Riyadhoh, Healing mental illness/Psychotherapy for drug addicts and cadre formation.